In Urban Areas of Sivas City the Determination of Bone Mineral Density Reference Values of Healthy Women Who Admitted to Cumhuriyet University Hospital Physical Medicine and Rehabilitation Outpatient Clinic - Gökay Tunç; Sevil Ceyhan Doğan; Sami Hizmetli; Emrullah Hayta (Galenos Yayinevi, 2014)
Objective: Osteoporosis and its results of fractures became a major health problem worldwide. Classification of OP by WHO based on Bone Mineral Density (BMD) measurements, and therefore it's definite measurement is the major tool for OP diagnosis. There are many ways to measure BMD. The mostly used technique is Dual-Energy-X-Ray Absorptiometry (DXA). Our aim in this study was to determine BMD reference values among healthy women in Sivas by using DXA. Materials and Methods: 350 volunteered women between ages 20-79 who came to Cumhuriyet University Department of Physical Medicine and Rehabilitation took place in this study. A survey form was used to exclude women who have problems that may lead to secondary osteoporosis, who are pregnant, breast feeding, being already treated for osteoporosis, and located outside Sivas county area. Women who met the criteria, are tested for their lumbar vertebrae (L1-L4) and left hip (femur neck, trochanter, total hip) BMD values by DXA method (Hologic QDR 4500 W). Results: Obtained BMD values classified in 6 groups based on decades (from 20-29 to 70-79). Obtained BMD values evaluated statistically and BMD reference values for age groups in Sivas county area are determined. Conclusion: In our study mean BMD values between ages 20-49 are stable for spinal and femoral levels. In our study mean BMD values for lumbar area varies between 1.01 gr/cm2 - 0.96 gr/cm2, for femoral area varies between 0.91 gr/cm2-0.89 gr/cm2 among women who are between 20-49 years old and reaches peak values in both femoral and spinal area between 30-39 age group. As a result we determined BMD reference values of healthy women in Sivas county area in our study. (Turkish Journal of Osteoporosis 2014;20: 104-9)